ENGLISH FOR SPECIFIC PURPOSES IN HIGHER EDUCATION: THE ROLE OF ENGLISH SPESIFIC PURPOSE FOR KNOWING A GOAL OF STUDENT IN MAJORING ENGLISH - Daulay, Ernita (VISION, 2023)
This paper discus about the role of English specific purpose for knowing a goal of students in majoring English . The main focus in the difficulties faced by the students in teaching English specific purpose . This paper is based on the data collected from some books and some journal that author search in website . The data shows that the student's goal majoring English after they learn about English specific purpose . Their difficulties are mainly due to the complicated materials and lack of practice . Other reason . relates to inappropriate textbooks ineffective methods , low interest , etc. another interesting reason is caused by their Indonesian background in which they cannot found goal after they collage , so this research will help the readers to aware about their future after collage .